Terrain Segmentation of Greece Using the Spatial and Seasonal Variation of Reference Crop Evapotranspiration - Vassilis Aschonitis; George Miliaresis; Kleoniki Demertzi; Dimitris Papamichail (Advances in Meteorology)
The study presents a combination of techniques for integrated analysis of reference crop evapotranspiration (ETo) in GIS environment. The analysis is performed for Greece and includes the use of (a) ASCE-standardized Penman-Monteith method for the estimation of 50-year mean monthly ETo, (b) cross-correlation and principal components analysis for the analysis of the spatiotemporal variability of ETo, (c) K-means clustering for terrain segmentation to regions with similar temporal variability of ETo, and (d) general linear models for the description of ETo based on clusters attributes. Cross-correlation revealed a negative correlation of ETo with both elevation and latitude and a week positive correlation with longitude. The correlation between ETo and elevation was maximized during the warm season, while the correlation with latitude was maximized during winter. The first two principal components accounted for the 97.9% of total variance of mean monthly ETo. K-means segmented Greece to 11 regions/clusters. The categorical factor of cluster number together with the parameters of elevation, latitude, and longitude described satisfactorily the ETo through general linear models verifying the robustness of the cluster analysis. This research effort can contribute to hydroclimatic studies and to environmental decision support in relation to water resources management in agriculture.